Managerial Supervision from a Qur’anic Perspective: Insights for Madrasah Leadership in Islamic Education - Zufriyatun; Ismunadi, Ali; Muttaqin, Sufyan; Mukhammad; Sadarman (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Exploration of the integration of Qur'anic values in managerial supervision is still rare. This research conducted in the Riau Islands proposes a Qur'an-based supervision framework that is proven to improve school management and support the achievement of the eight National Education Standards (SNP). In addition to improving school management, the integration of religious values also contributes to the establishment of a more holistic and quality learning environment. Using a qualitative approach, data were collected from nine madrasahs through interviews, observation and document analysis. The findings show that the application of Qur'anic values, such as tawhid (oneness of God), amanah (trust) and shura (deliberation), improves leadership effectiveness, managerial efficiency and learning quality. This model allows madrasahs to be more adaptive in facing modern educational challenges, such as limited resources and increased professionalism of educators. The implementation of Qur'an-based supervision not only improves institutional governance but also strengthens the moral and ethical aspects of educational leadership. Further research is needed to test the application of this model in various educational contexts to optimise its benefits, both in public schools and higher education institutions, so that Qur'an-based supervision can be applied more widely and effectively.